Accuracy of mandible-independent maxillary repositioning using pre-bent locking plates: a pilot study. Issue 7 (July 2020) - Imai, H.; Fujita, K.; Yamashita, Y.; Yajima, Y.; Takasu, H.; Takeda, A.; Honda, K.; Iwai, T.; Mitsudo, K.; Ono, T.; Omura, S.
Abstract: The double splint method is considered the gold standard for maxillary repositioning, but the procedure is lengthy and prone to error. Recent splintless methods have shown high repositioning accuracy; however, high costs and technical demands make them inaccessible to many patients. Therefore, a new cost-effective method of mandible-independent maxillary repositioning using pre-bent locking plates is proposed. Plates are bent on maxillary models in the planned position prior to surgery. The locations of the plate holes are replicated during surgery using osteotomy guides made from thermoplastic resin sheets. Pre-bent plates are subsequently fitted onto the maxilla, and plate holes are properly set to reposition the maxilla. The purpose of this study was to evaluate the accuracy of this method for maxillary repositioning and the reproducibility of the plate holes. Fifteen orthognathic surgery patients were evaluated retrospectively by superimposing preoperative simulations over their postoperative computed tomography models. The median deviations in maxillary repositioning and plate hole positioning between the preoperative plan and postoperative results were 0.43 mm (range 0–1.55 mm) and 0.33 mm (range 0–1.86 mm), respectively. There was no significant correlation between these deviations, suggesting that the method presented here allows highly accurate and reliable mandible-independent maxillary repositioning.